Effect of laser scanning speed on the microstructure, phase transformation and mechanical property of NiTi alloys fabricated by LPBF. (March 2022) - Guo, Wenqian; Feng, Bo; Yang, Ying; Ren, Yang; Liu, Yinong; Yang, Hong; Yang, Qin; Cui, Lishan; Tong, Xin; Hao, Shijie
Graphical abstract: Highlights: The effect of laser scanning speed on laser powder bed fusion fabricated NiTi alloys was systemically studied. The various microstructural factors on the martensite transformation are manifested. The martensite lattice shear mechanism endows the laser powder bed fusion fabricated NiTi alloy with superior tensile ultimate strain. The anisotropy of residual stress inside laser powder bed fusion fabricated NiTi is revealed by Synchrotron high-energy X-ray diffraction. Abstract: This study investigated the effects of laser scanning speed on the microstructure, phase transformation and properties of NiTi alloys fabricated by laser powder bed fusion (LPBF). In this study, the contributions of metallurgical factors under different scanning speeds, such as Ni evaporation, Ni4 Ti3 precipitation, dislocations and internal stress, to the transformation temperature and transformation latent heat were clarified through specially designed experiments. Ni evaporation is found to have the most profound effect, followed by precipitation. Increasing scanning speed is found to reduce Ni loss, thus cause less increase in the transformation temperature and transformation heat of the LPBF-NiTi alloys. Increasing scanning speed also increases the microstructure non-uniformity and thus widens the transformation temperature interval. The orientations of residual stress exhibit strong crystallographic stiffness dependence. The LPBF-NiTi alloys with different scanning speeds all exhibited high strains (>13.4%) and excellent shape memory effect. A LPBF-NiTi honeycomb structure exhibited 96% shape recovery rate after a 60% pre-compressive deformation. Besides, there is an optimum scanning speed for minimum porosity and smallest average pore size. However, the pore structure is found to have weak influence on the tensile behaviour of the LPBF-NiTi alloys, possibly due to the high defect tolerance of the martensitic transformation.